Modulation of extracellular matrix/adhesion molecule expression by BRG1 is associated with increased melanoma invasiveness - Saladi, Srinivas Vinod (BioMed Central, 2010)
BACKGROUND: Metastatic melanoma is an aggressive malignancy that is resistant to therapy and has a poor prognosis. The progression of primary melanoma to metastatic disease is a multi-step process that requires dynamic regulation of gene expression through currently uncharacterized epigenetic mechanisms. Epigenetic regulation of gene expression often involves changes in chromatin structure that are catalyzed by chromatin remodeling enzymes. Understanding the mechanisms involved in the regulation of gene expression during metastasis is important for developing an effective strategy to treat metastatic melanoma. SWI/SNF enzymes are multisubunit complexes that contain either BRG1 or BRM as the catalytic subunit. We previously demonstrated that heterogeneous SWI/SNF complexes containing either BRG1 or BRM are epigenetic modulators that regulate important aspects of the melanoma phenotype and are required for melanoma tumorigenicity in vitro. RESULTS: To characterize BRG1 expression during melanoma progression, we assayed expression of BRG1 in patient derived normal skin and in melanoma specimen. BRG1 mRNA levels were significantly higher in stage IV melanomas compared to stage III tumors and to normal skin. To determine the role of BRG1 in regulating the expression of genes involved in melanoma metastasis, we expressed BRG1 in a melanoma cell line that lacks BRG1 expression and examined changes in extracellular matrix and adhesion molecule expression. We found that BRG1 modulated the expression of a subset of extracellular matrix remodeling enzymes and adhesion proteins. Furthermore, BRG1 altered melanoma adhesion to different extracellular matrix components. Expression of BRG1 in melanoma cells that lack BRG1 increased invasive ability while down-regulation of BRG1 inhibited invasive ability in vitro. Activation of metalloproteinase (MMP) 2 expression greatly contributed to the BRG1 induced increase in melanoma invasiveness. We found that BRG1 is recruited to the MMP2 promoter and directly activates expression of this metastasis associated gene. CONCLUSIONS: We provide evidence that BRG1 expression increases during melanoma progression. Our study has identified BRG1 target genes that play an important role in melanoma metastasis and we show that BRG1 promotes melanoma invasive ability in vitro. These results suggest that increased BRG1 levels promote the epigenetic changes in gene expression required for melanoma metastasis to proceed.